Development of Scientific-Based Student Worksheets (LKPD) Using the Discovery Learning Model to Improve Science Skills of Sixth Grade Elementary Students - Efa Rosalina Sitorus; Ely Djulia; Sumarno (Didaktika: Jurnal Kependidikan, 2025)
This research aims to describe: Validity and practicality of scientific-based LKPD using the Discovery Learning model. This research is development research using the ADDIE model which was carried out in class VI of SDN 173662. The research results obtained are: The module developed has been categorized as Valid, Practical and Effective. Based on the validation results of the material expert, the category was "Very Good" with an average percentage of 81.7%, the validation results of the language expert stated that the LKPD developed was in the "Very Good" category with an average percentage of 95%. Furthermore, the learning expert revealed that the LKPD developed was in the "Very Good" category with an average percentage of 86.7%, so it was concluded that the LKPD developed was very valid. Furthermore, based on teacher responses of 90% and student responses of 96%, the LKPD developed was practical to use. So it can be concluded that the student worksheet developed is valid and practical to use in class VI.